Assessing The Relationship Between Emotional Intelligence And Employee Productivity: A Case Study Of Manufacturing Workers In Nagpur (Journal of Namibian Studies : History Politics Culture, 2023)
This study looks at the manufacturing industry in Nagpur, India, and how emotional intelligence (EI) relates to worker output. Given the ever-changing nature of the manufacturing industry and the difficulties that come with it, it is crucial to comprehend how EI may boost productivity. Combining quantitative surveys with qualitative interviews, the research adopts a mixed-methods technique to acquire complete data. The numerical component comprises surveying a cross-section of Nagpur's industrial workforce using standardised EI and productivity questionnaires. Output, efficiency, and quality of work are some of the productivity measures that are measured, along with other aspects of emotional intelligence including self-awareness, self-regulation, social awareness, and relationship management. To determine the nature and direction of the connection between EI and production, statistical methods such as regression and correlation analysis are used. Also, in order to learn more about how emotional intelligence affects industrial workers' productivity, qualitative interviews are carried out simultaneously. These in-depth interviews give light on the many manifestations of emotional intelligence, the effect it is believed to have on work performance, and the difficulties that arise when trying to put it into practice. The hope is that this study will add to theoretical knowledge and practical consequences by combining quantitative and qualitative data. In order to help HR professionals, managers, and lawmakers improve organizational effectiveness and worker well-being in similar industrial settings, this study sheds light on the complex relationship between emotional intelligence and employee productivity in Nagpur's manufacturing sector.